Kynurenine pathway metabolism and the neurobiology of treatment-resistant depression: Comparison of multiple ketamine infusions and electroconvulsive therapy. (May 2018) - Allen, A.P.; Naughton, M.; Dowling, J.; Walsh, A.; O'Shea, R.; Shorten, G.; Scott, L.; McLoughlin, D.M.; Cryan, J.F.; Clarke, G.; Dinan, T.G.
Abstract: Current first-line antidepressants can take weeks or months to decrease depressive symptoms. Low dose ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, shows potential for a more rapid antidepressant effect, with efficacy also evident in previously treatment-resistant populations. However, a greater understanding of the physiological mechanisms underlying such effects is required. We assessed the potential impact of ketamine infusion on neurobiological drivers of kynurenine pathway metabolism in major depression (HPA axis hyperactivity, inflammation) in patients with treatment-resistant depression compared to gender-matched healthy controls. Furthermore, we assessed these biomarkers before and after electroconvulsive therapy (ECT), which is currently the gold standard for management of treatment-resistant depression. As previously demonstrated, treatment with ketamine and ECT was associated with improved depressive symptoms in patients. At baseline, waking cortisol output was greater in the ECT cohort, kynurenine was greater in the ketamine cohort, and kynurenic acid was lower in patients compared to healthy controls, although inflammatory markers (IL-6, IL-8, IL-10 or IFN-γ) were similar in patients and controls. Furthermore, in patients who responded to ECT, the cortisol awakening response was decreased following treatment. Despite a trend towards reduced kynurenine concentrations in those who responded to ketamine, ketamine was not associated with significant alterations in any of the biomarkers assessed. Highlights: Plasma kynurenine was not altered following successful ketamine response. Kynurenic acid was reduced in patients with treatment-resistant depression. In patients who responded to ECT, the cortisol awakening response was decreased.